Penilaian terhadap pengajaran syariat Islam oleh al-Hallaj, Hamzah al-Fansuri, dan Shamsuddin al-Sumatera’i - Rohaimi Rastam,; Yusri Mohamad Ramli,; Mohd Syukri Yeoh Abdullah, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
Integration between religious law and spiritual dimension is an equilibrial perfection in Islam, therefore became continuoslyy reminded by Muslim scholars from time to time. Yet, some researchers claim it's contradiction, whereas Muslim Sufi scholars such as al-Hallaj, Hamzah al-Fansuri, and Shamsuddin al-Sumatera'i has firm statement in it's inseparable. Thus, the purpose of this article is to evaluate the teaching on Islamic law by al-Hallaj, Hamzah al-Fansuri, and Shamsuddin al- Sumatera’i' based on their own sayings and actions.